The Relationship Between Adat Law & National Law on Marriage in Indonesia - Kusumo, Vonny Kristanti (Veteran Law Review, 2023)
Indonesia is an archipelagic country that has a pluralistic society consisting of diverse ethnicities, customs and cultures. Each group lives by using rules nor established good norms written or unwritten and originating from habit Indonesian society or the customs in which it is used to regulate life behavior _ society , which is often referred to as "customary" or "customary law". As a country in the form of a republic , Indonesia is regulated by law in statutory regulations , where these statutory regulations are written laws. To carry out a marriage, for a country and nation like Indonesia it is It is absolute that there is a National Marriage Law that also accommodates principles and provide a legal basis for marriage which has been the guideline and has been applied to various groups in society us . But marriage in Indonesia can also be carried out with the customary law of certain indigenous communities in accordance with the rules or norms that bind them hereditary.